Simulation Evidence of Hexagonal‐to‐Tetragonal ZnSe Structure Transition: A Monolayer Material with a Wide‐Range Tunable Direct Bandgap. Issue 12 (28th October 2015) - Li, Lei; Li, Pengfei; Lu, Ning; Dai, Jun; Zeng, Xiao Cheng
Abstract : 2D material with tunable direct bandgap in the intermediate region (i.e., ≈2–3 eV) is key to the achievement of high efficiency in visible‐light optical devices. Herein, a simulation evidence of structure transition of monolayer ZnSe from the experimental pseudohexagonal structure to the tetragonal structure (t‐ZnSe) under lateral pressure is shown, suggesting a possible fabrication route to achieve the t‐ZnSe monolayer. The as‐produced t‐ZnSe monolayer exhibits highly tunable bandgap under the biaxial strains, allowing strain engineering of t‐ZnSe's bandgap over a wide range of 2–3 eV. Importantly, even under the biaxial strain up to 7%, the t‐ZnSe monolayer still keeps its direct‐gap property in the desirable range of 2.40–3.17 eV (corresponding to wavelength of green light to ultraviolet). The wide‐range tunability of direct bandgap appears to be a unique property of the t‐ZnSe monolayer, suggesting its potential application as a light‐emitting 2D material in red–green–blue light emission diodes or as complementary light‐absorption material in the blue–yellow region for multijunction solar cells. The straddling of the band edge of the t‐ZnSe monolayer over the redox potential of water splitting reaction also points to its plausible application for visible‐light‐driven water splitting. Abstract : Simulation evidence for a structural transition in 2D ZnSe, from the pseudohexagonal to the tetragonal structure (t‐ZnSe) under lateral pressure, is demonstrated. The 2D t‐ZnSe exhibits highly tunable bandgap from 2 to 3 eV under the biaxial strains, suggesting its potential application as light‐emitting material in red–green–blue light emission diodes or for visible‐light‐driven water splitting through suitable band alignment.